2014
DOI: 10.4103/2249-4863.148089
|View full text |Cite
|
Sign up to set email alerts
|

Management of emergencies in general practice: Role of general practitioners

Abstract: Introduction:Management of emergencies is an integral part of primary care. Being first contact care providers general practitioners may encounter any type of emergency. Acute attacks of asthma, myocardial infarction, anaphylactic shock, hypoglycemic coma, convulsions, head injuries and trauma are some of the common emergencies encountered by GPs. Updated knowledge, communication and procedural skills, trained paramedical staff, necessary equipment and medications and appropriate practice organization are vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 7 publications
(15 reference statements)
0
34
0
Order By: Relevance
“…83 Moreover, the primary care centers are generally ill-equipped to manage emergency cases, which are generally referred to urban multi-specialty hospitals. 84 This continuous inflow of patients often leads to overcrowding near the emergency department of urban hospitals, which has pre-existing limitations and challenges. 83 Understanding this cycle of emergency management can better inform how potential strategies can be developed and implemented to strengthen emergency management and referral services.…”
Section: Discussionmentioning
confidence: 99%
“…83 Moreover, the primary care centers are generally ill-equipped to manage emergency cases, which are generally referred to urban multi-specialty hospitals. 84 This continuous inflow of patients often leads to overcrowding near the emergency department of urban hospitals, which has pre-existing limitations and challenges. 83 Understanding this cycle of emergency management can better inform how potential strategies can be developed and implemented to strengthen emergency management and referral services.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of emergencies and the rarity of some of them make it difficult for physicians to be updated and competent in emergency care provision. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 6 7 8 9 ] This wide variation of encountered emergency cases poses a challenge for physicians to be properly updated and competent in emergency medicine. [ 10 ] Informative literature describing and assessing the impact of factors such as PHC physicians’ emergency care-related knowledge, attitude, and practice (KAP) is, unfortunately, deficient both nationally and internationally.…”
Section: Introductionmentioning
confidence: 99%
“…At the bedside, doctors identify shock using clinical history, health status, vital signs, examination, and easily available investigations such as urine output and blood lactate [3,4]. Appling a clinical diagnostic algorithm using these components which are generated based on the physician expertise is a way to improve diagnostic accuracy [5,6]. Recently there has been increased interest in evaluating the role of clinician experience, otherwise known as gestalt, in the assessment of disease [7] or prediction of the treatment failure [8], and some studies have concluded that emergency physician gestalt is not sufficiently accurate [9,10].…”
Section: Introductionmentioning
confidence: 99%